Caring for Children While Working in Agriculture—The Perspectiveof Farmworker Parents. Issue 4 (2nd October 2017) - Liebman, Amy K.; Simmons, Juliana; Salzwedel, Marsha; Tovar-Aguilar, Antonio; Lee, Barbara C.
ABSTRACT: Access to safe, off-farm childcare is often a challenge for farmworkers with young children and is likely to become an increasingly salient barrier as more agricultural workers migrate together with families and as the number of women entering the agricultural workforce increases. Agriculture is one of the most hazardous industries, and the presence of young children in the workplace puts them at risk. To better understand the current nature of childcare for farmworker families and the challenges to accessing services, this project facilitated in-person surveys with 132 parents in three communities in Florida. A convenience sample that intentionally targeted parents living and working in areas with limited access to Migrant and Seasonal Head Start facilities was used to recruit participants. Most participants reported childcare access as a challenge. They expressed a desire to work in an area based on childcare availability. These findings offer agribusiness leaders important data to consider. They also suggest that industry support of childcare may be an important workforce investment. Findings indicate that high quality, affordable off-farm childcare services could serve as a means for attracting farmworkers to regions currently experiencing labor shortages. Additional research is warranted to explore this subject in diverse geographic areas.